2017
DOI: 10.20944/preprints201705.0107.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental, Human Health and Socio-Economic Effects of Cement Powders: the Multicriteria Analysis as Decisional Methodology

Abstract: The attention to sustainable-related issues has grown fast in recent decades. The experience gained with these themes reveals the importance of considering this topic in the construction industry, which represents an important sector in the world. This work consists on conducting a multicriteria analysis of four cement powders, with the objective of calculating and analysing the environmental, human health and socio-economic effects of their production processes. The economic, technical, environmental and safe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…H 2 : The economy has a positive effect on the implementation of EMS Irhoma et al (2014) that the social aspects referred to are more about leadership and poor management, external political constraints of organizational culture. Likewise, the results of previous research also support the assumption of a relationship between social aspects and the implementation of an environmental management system, among others, by Liboni and Cezarino (2012) Integrated Report Committee (2014), Behera (2015), Struwig and Lillah (2016), Moretti et al (2017) and Nanok and Onyango (2017). H 3 : Social has a negative effect on the implementation of EMS 2006) is that using SEM allows analysis of a series of relationships simultaneously so as to provide statistical efficiency.…”
Section: Hypothesissupporting
confidence: 74%
See 2 more Smart Citations
“…H 2 : The economy has a positive effect on the implementation of EMS Irhoma et al (2014) that the social aspects referred to are more about leadership and poor management, external political constraints of organizational culture. Likewise, the results of previous research also support the assumption of a relationship between social aspects and the implementation of an environmental management system, among others, by Liboni and Cezarino (2012) Integrated Report Committee (2014), Behera (2015), Struwig and Lillah (2016), Moretti et al (2017) and Nanok and Onyango (2017). H 3 : Social has a negative effect on the implementation of EMS 2006) is that using SEM allows analysis of a series of relationships simultaneously so as to provide statistical efficiency.…”
Section: Hypothesissupporting
confidence: 74%
“…Likewise Chatzinikolaou and Ventikos (2014) in assessing the environmental impacts of ships from a life cycle perspective presents an assessment of the environmental impacts of the most important air emissions produced by oil tankers. Several previous studies also showed the relationship between ecological aspects and the implementation of environmental management systems, among others, by Liboni and Cezarino (2012), Integrated Report Committee (2014), Struwig and Lillah (2016), Moretti et al (2017) and Nanok and Onyango (2017).…”
Section: The Concept Of An Environmental Management System In Indonesiamentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, concrete interrupts, changes, and destroys ecologies that support fertilization, pollination, oxygen production, and water purification. Air pollution is also a significant by-product during production, causing acute dose-related respiratory problems near production sites for both workers and the wider populace (Moretti, Di Mascio, & Bellagamba, 2017).…”
Section: Explain Howmentioning
confidence: 99%
“…As shown by much of the literature, life cycle methodologies underpin Circular Economy strategies but also highlight some weaknesses (Notarnicola et al 2016 ; Peña et al 2021 ) which can be overcome through the proper use of multi-criteria approaches. Recent studies, in fact, have demonstrated that multi-criteria approaches are a useful and effective decision aiding support tools to assess the potentials of new sustainable construction materials (Moretti et al 2017 ; Kurda et al 2019 ; Saeli et al 2020 ). In the selection of novel materials, the need to consider simultaneously contradictory and often uncertain aspects—like technological, environmental, and economic ones—makes the multi-criteria approach extremely suitable (Micale et al 2017 ), even if to date, most of the available literature on recycling SCG in construction materials has not considered in multi-criteria approaches (Saberian et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%